Nonlinear Numerical Modeling of the Wire-Ring Net for Flexible Barriers - Zhixiang Yu; Chun Liu; Liping Guo; Lei Zhao; Shichun Zhao (Shock and Vibration)
To investigate the nonlinear mechanical behavior of the wire-ring net, this paper presents a new numerical model that can collectively consider equivalence between numerical and actual wire rings. Quasi-static tests, including tensile tests on steel wires and one-ring specimens, and puncturing tests on net specimens were conducted. Based on the test results, the axial constitutive curves of steel wires were obtained. The linear correlation equations for the breaking loads of the one-ring specimens and the puncturing strength of wire-ring nets were established, both of which were related to the number of windings. The wire rings were modeled via an equivalent structure with a single winding and a circular cross section. Equivalence between the numerical and actual wire rings in terms of bending and tensile strength, total mass, contact with sliding friction, and rupture behavior were also derived and presented. In particular, the emphasis was on simulating the flattening effect, a phenomenon rarely accounted for in conventional numerical models. All dominant factors were reflected in a model with the material law by the input of material parameters. The proposed mechanical model was calibrated and verified by the data from the tests of the wire-ring net. The calibrated mechanical model is also shown to successfully simulate a full-scale test of a flexible rockfall protection barrier according to the ETAG027 standard.